Cultural Poetics in Hamlet: A Critical Reading - Dr. Yassir Mohammed Nasr Ali; محمد ياسر (مجلة اداب ذي قار, 2025)
This paper proposes to critically address William Shakespeare's  Hamlet as a discourse embedded in cultural configurations and power dynamics. The paper problematizes traditional methods of reading the drama while inviting new avenues of critical exploration. With this in mind, the researchers attempt a close reading of the text, and anchor their interpretive acts upon engagements with the Elizabethan and Jacobean context. The paper, therefore, is a contribution to contemporary Shakespeare Studies, and a call for revising a great deal of what is/has been taken for granted in the humanities.